Abundance and biofilm formation capability of Vibrio cholerae in aquatic environment with an emphasis on Hilsha fish (Tenualosa ilisha) - Dey, Subarna Sandhani; Hossain, Zenat Zebin; Akhter, Humaira; Jensen, Peter K. M.; Begum, Anowara (Frontiers in Microbiology, 2022)
The potential deadly and sporadic diarrhea causing agent, Vibrio cholerae is present in a great number in the freshwater aquatic environment and can be transmitted to human by different aquatic organisms. In perspective of Bangladesh, an anadromous fish species Hilsha (Tenualosa ilisha) can act as a transmission vehicle of V. cholerae from the aquatic to household kitchen-environment. The present study was carried out to investigate the presence of V. cholerae in aquatic habitat of Bangladesh with a major emphasis on freshly caught Hilsha fish, along with river water and plankton samples from the fish capture site. The study also detected the biofilm formation capability of V. cholerae within Hilsha fish that might help the transmission and persistence of the pathogen in aquatic habitat.. Twenty out of 65 freshly caught fish (30.8%) and 1 out of 15 water samples (6.67%) showed the presence of V. cholerae and none of the plankton samples were positive for V. cholerae. The isolated strains were identified as non-O1 and non-O139 serogroups of V. cholerae and contain some major toxin and virulence genes. A few strains showed cellular cytotoxicity on HeLa cell line. All strains were able to form biofilm on microtiter plate and the detection of three genes related to biofilm formation (vpsA, vpsL and vpsR) was also assayed using qPCR. In this study, the in vitro biofilm formation ability of the isolated strains may indicate the long term persistence of V. cholerae in different parts of Hilsha fish. The abundance of V. cholerae only in freshly caught Hilsha fish and absence of the pathogen in the surrounding aquatic environment could stipulate the role of Hilsha fish as one of the major transmission routes of V. cholerae from freshwater aquatic environment of Bangladesh to household kitchen-environment.